1980
DOI: 10.1093/nar/8.12.2787
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic separation of a class of nucleosomes enriched in HMG 14 and 17 and actively transcribed globin genes

Abstract: Monomer nucleosomes from chick erythrocytes can be fractionated according to their electrophoretic mobility in (comparatively) high salt acrylamide gels. We show that the fractionation is based predominantly on differences in charge. The monomer heterogeneity persists even when the nucleosomes are trimmed down to 145 bp with Exo III or when H1 and H5 are removed. The slowest migrating monomers are associated with HMG 14 and 17; however, we do not believe that these proteins are entirely responsible for the alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 19 publications
2
22
1
1
Order By: Relevance
“…These results confirmed and extended earlier findings which suggested a preferential association of HMG14/17 with transcribed genes in vivo [6][7][8].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirmed and extended earlier findings which suggested a preferential association of HMG14/17 with transcribed genes in vivo [6][7][8].…”
Section: Introductionsupporting
confidence: 92%
“…Since the presence of HMG14 or 17 on the nucleosomal array during digestion by staphylococcal nuclease partially protects the linker DNA from 'nibbling' by the nuclease [3,8,18,22], our hypothesis appears to be sufficient to explain the phenomenon of preferential in vitro HMG binding to mononucleosomes which contained HMGs at the time of their excision from chromatin by staphylococcal nuclease.…”
Section: Discussionmentioning
confidence: 96%
“…HMG 14 and HMG 17 are categorized as structural proteins that are associated wth potentially active regions of chromatin (7). Studies have shown that mononucleosomes preferentially released from chromatin by micrococcal nuclease digestion contain HMG 14 and HMG 17 and are also enriched in expressed DNA sequences (7,8). Reconstitution studies provide further evidence that active or potentially active regions of chromatin, as identified by DNase I sensitivity, are associated with the HMG14 and HMG 17 (9,10).…”
mentioning
confidence: 99%
“…Although the general structure of the nucleosome core particle is fairly well established (3)(4)(5)(6), little is known about the dynamics ofthe structure and the interaction ofpotential effector proteins such as ubiquitin or the high mobility group (HMG) nonhistone chromosomal proteins. HMG 14 and HMG 17 are categorized as structural proteins that are associated wth potentially active regions of chromatin (7). Studies have shown that mononucleosomes preferentially released from chromatin by micrococcal nuclease digestion contain HMG 14 and HMG 17 and are also enriched in expressed DNA sequences (7,8).…”
mentioning
confidence: 99%
“…Albanese and Weintraub (5) observed that chick erythrocyte nucleosomes that are enriched in globin gene DNA sequences migrate more slowly than core particles on polyacrylamide gels. Such nucleoprotein particles contained longer than core particle length DNA and were associated with HMG 14 and 17.…”
Section: Introductionmentioning
confidence: 99%